Male sexual dysfunctions in homosexuals: an integrative review (Research, Society and Development, 2021)
Introduction: Sexual dysfunction is a common problem for men and women. For this reason, it came to be seen as a public health problem. However, we live in a society where it is still restricted to talk about sexual behavior, especially in relation to homosexuality, defined as sexual attraction between people of the same sex, which has been present since the beginning of civilization. Objective: It was to know the prevalence of sexual dysfunctions in homosexual individuals. Methodology: this is an intergrative review, the data resulting from a survey carried out between March 2020 and June 2021 in the PubMed, BVS and PEDro databases. For this, systematic review articles and randomized clinical trials published in the last 16 years were included. These report on male sexual dysfunction in homosexuals, prevalence, and treatment of sexual dysfunctions. Results: After a detailed study, the importance of further research on the topic addressed was analyzed, as misinformation and lack of care prevail in many cases. Final Consideration: therefore, it is essential to provide information and guidance on preventive care and multidisciplinary treatment, so that there is a decrease in prevalence rates, and that with this this public starts to have a better quality of life, and a sex life more satisfying and pleasurable.